MATLAB/Simulink modelling and simulation of 9-level cascaded h-bridge multilevel inverter with mismatched DC sources - W. V. Yong; M. S. Chye; Y. C. Tan; S. L. Ong; J. H. Leong (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents a MATLAB/Simulink model for a 9-level cascaded H-bridge multilevel inverter with mismatched DC voltage sources. The impact of mismatched DC voltage sources on the performance of the 9-level CHBMI is investigated. Due to the mismatched voltages among DC voltage sources, the output fundamental voltage is different from the input reference voltage. To address this problem, a switching-angle calculation technique that accounts for mismatched as well as varying DC voltage sources is demonstrated. The switching angles obtained using this technique is able to produce the desired output fundamental voltage for a wide range of input reference voltages. Since this switching-angle calculation technique does not require complex iterative computation, it has the potential for real-time implementation.